Corporate Values, Operations of Indian Multinational Companies in Thailand Using Confirmatory Factor Analysis - Mahamud, Tosaporn (International Journal of Psychosocial Rehabilitation, 2020)
This research is mixed method research, which is the study of the organization values, operating of the Indian multinational corporations in Bangkok Metropolis. The purpose of the research aims to analyze the confirmatory factors for the organization values of their employees' performance by using the companies’ CFA Confirm Factor Analysis to compare the organization values in the performance of the employees of the Indian multinational corporations in Bangkok Metropolis , classified by common characteristics in order to study the guidelines for developing organization values related to performance of the employees of the Indian multinational corporations in Bangkok Metropolis , dividing them into four aspects, including career value, individual value, organization culture’s value and main value. Data collection from questionnaires distribution of employees of the Indian companies in Bangkok Metropolis, in-depth interviews with its staff as well as groups seminar. The results of the study found that the analysis of confirmatory factors, factor loading, and professional values, personal values, corporate culture values, and core values comparable performance is at a similar standard. The approach of developing a multinational company is as high as the potential for development to meet other transnational corporations. The theoretical and methodological issues related to the application of organizational innovation are discussed in these findings. As a result, mutual understanding in work culture and internationalization in co-operation will benefit the development of efficiency and the growth of the organization in the future.